Patterns of epiphany : from Wordsworth to Tolstoy, Pater, and Barrett Browning - Bidney, Martin (Southern Illinois University Press, 1997)
Probing those puzzling but privileged moments, those sudden gifts of vision and illumination when the feeling of life intensifies and the senses quicken, Martin Bidney employs a new approach to analyze epiphanies in the poems, novels, short stories, and essays of eight nineteenth-century writers. Taking his cue from the French philosopher Gaston Bachelard, he postulates that any writer's epiphany pattern usually shows characteristic elements (earth, air, fire, water), patterns of motion (pendular, eruptive, trembling), and/or geometric shapes. Bachelard's analytic approach involves studying patterns of perceived experience - phenomenology - but unlike most phenomenologists, Bidney does not speculate on internal processes of consciousness. Instead, he concentrates on literary epiphanies as objects on the printed page, as things with structures that can be detected and analyzed for their implications.